Why Life Gets Better After Age 50, for Some: Mental Well-Being and the Social Norm of Work - Coen van de Kraats; Titus Galama; Maarten Lindeboom; Zichen Deng (Institute of Labor Economics (IZA), 2024)
We provide evidence that the social norm (expectation) that adults work has a substantial detrimental causal effect on the mental well-being of unemployed men in mid-life, as substantial as, e.g., the detriment of being widowed. As their peers in age retire and the social norm weakens, the mental well-being of the unemployed improves. Using data on individuals aged 50+ from 10 European countries, we identify the social norm of work effect using exogenous variation in the earliest eligibility age for old-age public pensions across countries and birth cohorts.
Keywords: I10; I31; J60; D63; 330; mental well-being; social norm of work; retirement institution